The Role of Anatomic Dimensions in the Development of Primary Small Bowel Volvulus, NorthWestern Ethiopia: A Case-control Study - Bayeh A; Abegaz B (Open Access Surgery, 2022)
Agegnehu Bayeh,1 Belta Abegaz2 1Department of Surgery, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 2Department of Biomedical Sciences, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, EthiopiaCorrespondence: Agegnehu Bayeh, Department of Surgery, College of Medicine and Health Sciences, Bahir Dar University, PO Box 79, Bahir Dar, Ethiopia, Tel +251 923486085, Email agegnehuberie@gmail.comBackground: Anatomic dimensions of jejunum and ileum have been known to vary among individuals; however, their role in the development of primary small bowel volvulus was barely studied. The main objective of this study was to assess the role of small bowel anatomic dimensions in the development of primary small bowel volvulus.Methods and Materials: A prospective case-control study to compare small bowel anatomic dimensions between patients with intraoperatively confirmed primary small bowel volvulus (cases) and control groups was conducted from December 2019 to December 2020 at Tibebe Ghion Specialized Hospital (TGSH) and Felege Hiwot Comprehensive Specialized Hospital (FHCSH), two referral hospitals in Bahir Dar city, NorthWestern Ethiopia. Jejunoileal length, mesenteric length, mesenteric root, and the ratio of small bowel mesenteric length to small bowel mesenteric root were compared between cases and controls using unpaired Student’s t-test, Welch’s t-test, or Mann–Whitney U-test at p-value ≤ 0.05 (two-sided).Results: A total of 78 participants (39 cases and 39 controls) were included and analyzed in the study. Twenty-nine (74.4%) cases and 18 (46.2%) controls were males. The mean ages in years for cases and controls were 40.2 (SD=14.1) and 46.6 (SD=15.0), respectively. The study showed that patients with primary small bowel volvulus had statistically significantly longer small bowel length and small bowel mesenteric length than controls, but small bowel mesenteric root was found not to be statistically significantly different between cases and controls. The Mann–Whitney U-test for the comparison of the ratio of small bowel mesenteric length to small bowel mesenteric root showed that the mean rank was statistically significantly higher in cases than in the controls.Conclusion: A longer small bowel with longer mesentery and higher small bowel mesenteric length to small bowel mesenteric root ratio is highly likely to predispose individuals to primary small bowel volvulus.Keywords: bowel obstruction, intestine, jejunum, ileum, human anatomy, mesentery